PERKAWINAN DALAM LANDSCAP KEINDONESIAAN (PENDEKATAN ANTROPOLOGI, SOSIOLOGI, HUKUM) - Soeprijanto, Troeboes (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2024)
The development of human civilization/growth and development, humans, Koentjaraningrat, in his introduction to anthropology, published by Rineka Cipta, eighth edition, last published in 1981, explains that "From a biological point of view, humans are only one type of creature among more than a million other types of creatures, who have ever or still occupy this world. In the 19th century, biologists, especially Charles Robert Darwin (born 12 February 1809), announced his theory about the process of human biological evolution. According to his theory, the oldest forms of human life on the face of the earth consisted of very simple one-cell creatures such as protozoa/a kind of tadpole (child of a frog), over time over millions, billions and years, they emerged and developed. "living forms in the form of creatures with self-organization (forming groups) that are increasingly complex over time, and in recent times have developed or evolved, finally becoming apes and humans." Geographically, Indonesia is an area that stretches across the surface, in the form of land, sea and air, space, including sea/water, as well as the natural riches contained therein, stretching between the continent of Asia to the northwest and the continent of Australia to the southeast, and between the Indian Ocean and the Pacific Ocean, located at 6 degrees north latitude – 11 degrees south latitude and 95 degrees east longitude - 141 east longitude. As an archipelagic area (archipelago area) it has 17,508 islands, consisting of large islands and small islands, there are 8 large islands (Papua, Kalimantan, Sumatra, Sulawesi, Java Timor, Halmahera, Seram) and thousands of islands small, around 17,500, stretching from Sabang (west) to Merauke (east), Miangas (north), Rote (south), there are thousands of biological riches (living creatures), both vegetable (plants), animal (animals) including flora/plants , fauna/animals, characterized by a tropical/warm climate with 2 seasons, namely rainy and dry. The preamble to the 1945 Law provides both implied (understanding the idea) and explicit (understanding the written meaning) guidelines for the protection of all life in Indonesian society (lower society) in all aspects of life, including marriage.